2003
DOI: 10.1074/jbc.m305107200
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Regulation of Mitogen-activated Protein Kinase Signaling in Articular Cartilage

Abstract: Articular chondrocytes respond to mechanical forces by alterations in gene expression, proliferative status, and metabolic functions. Little is known concerning the cell signaling systems that receive, transduce, and convey mechanical information to the chondrocyte interior. Here, we show that ex vivo cartilage compression stimulates the phosphorylation of ERK1/2, p38 MAPK, and SAPK/ERK kinase-1 (SEK1) of the JNK pathway. Mechanical compression induced a phased phosphorylation of ERK consisting of a rapid indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
86
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 119 publications
(96 citation statements)
references
References 50 publications
(59 reference statements)
9
86
0
1
Order By: Relevance
“…The recent studies found that p38 and ERK MAPK pathways were involved in TGF-ß1-induced chondrogenesis of ATDC5 cells [54,55], whereas Sox9 induction by fibroblast growth factors in chondrocytes and undifferentiated mesenchymal cells was mediated by the ERK MAPK pathway [56]. Moreover, it was recently demonstrated that the MAPK signal pathway was activated in cartilage by static compressive loading with a rapid induction of ERK and p38 MAPK pathways and a delayed stimulation of SAPK/JNK MAPK pathway [57]. Therefore, three major MAPK pathways could be activated in BM-MSCs by dynamic compressive loading.…”
Section: Discussionmentioning
confidence: 99%
“…The recent studies found that p38 and ERK MAPK pathways were involved in TGF-ß1-induced chondrogenesis of ATDC5 cells [54,55], whereas Sox9 induction by fibroblast growth factors in chondrocytes and undifferentiated mesenchymal cells was mediated by the ERK MAPK pathway [56]. Moreover, it was recently demonstrated that the MAPK signal pathway was activated in cartilage by static compressive loading with a rapid induction of ERK and p38 MAPK pathways and a delayed stimulation of SAPK/JNK MAPK pathway [57]. Therefore, three major MAPK pathways could be activated in BM-MSCs by dynamic compressive loading.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the milder stimulation of c-Fos and c-Jun (Group M3) in response to the dynamic loading compared with static loading may be related to the lower amplitude of the initial deformation applied to the cartilage in dynamic loading. c-Fos and c-Jun are downstream of the mitogen-activated protein kinases (39), which have been identified as mechanically sensitive to static compression (40,41). Extracellular signal-regulated kinases 1 and 2 become maximally phosphorylated within 10 min of application of a 50% static compression, indicating an immediate response to the changing environmental conditions (40).…”
Section: Discussionmentioning
confidence: 99%
“…Intracellular calcium release, cAMP, and the phospholipase C pathway have been implicated for aggrecan gene up-regulation in response to static compression in cartilage explants (25). Static compression also increased ERK1/2 phosphorylation within minutes of application, with sustained increases during 24 h of compression (26). Although such signaling pathways have been identified in the mechanical regulation of aggrecan gene expression, less is known about chondrocyte gene expression patterns of other ECM-related molecules or whether common upstream signaling pathways are responsible for their regulation.…”
mentioning
confidence: 99%